THE FLOUTINGS OF GRICE’S MAXIMS TO CREATE HUMOR ON FRIENDS SEASON 9 - Ittaqullah; Yose Rianugraha (Conscientia, 2022)
This research concentrates on the floutings of Grice’s maxims found in the creation of verbally expressed humor in an American situational comedy entitled Friends season 9. Therefore, this research aimed to find out how flouting Grice’s maxims might contribute to creating some humorous conversations on Friends season 9. The transcripts of the characters’ utterances from Friends season 9 served as the data for this study. In order to answer the research question, the qualitative method is used in analyzing the data in the form of words. The findings show that all of Grice’s maxims were flouted in creating some of the humor of the sitcom; there are 86 floutings found. The most frequently flouted maxim was the maxim of Quality (36 times). The results also reveal that by applying the three major theories of humor (incongruity, superiority, psychic release), flouting Grice’s maxims might create humor because of three reasons. The first reason is that the floutings show/illustrate the character’s defects or suffering. There are misfortunes or unpleasant experiences of the sitcom’s characters that the audience laughs at (superiority-based humor). The second reason is that the floutings go against the expectation from the audience that what happens in the sitcom is different from what is expected (incongruity-based humor). The final explanation is that the floutings present a sexually-related subject. By presenting the subject, laughter is evoked by the relief from the removal, albeit momentary, of the restraint (psychic release-based humor). Keywords: Cooperative Principle, Floutings, Verbal Humor, Friends